Implication of Inflammation and Epigenetic Readers in Coronary Artery Remodeling in Patients With Pulmonary Arterial Hypertension. Issue 8 (August 2017) - Meloche, Jolyane; Lampron, Marie-Claude; Nadeau, Valérie; Maltais, Mélanie; Potus, François; Lambert, Caroline; Tremblay, Eve; Vitry, Géraldine; Breuils-Bonnet, Sandra; Boucherat, Olivier; Charbonneau, Eric; Provencher, Steeve; et al.
Abstract : Objective—: Pulmonary arterial hypertension (PAH) is a vascular disease not restricted to the lungs. Many signaling pathways described in PAH are also of importance in other vascular remodeling diseases, such as coronary artery disease (CAD). Intriguingly, CAD is 4× more prevalent in PAH compared with the global population, suggesting a link between these 2 diseases. Both PAH and CAD are associated with sustained inflammation and smooth muscle cell proliferation/apoptosis imbalance and we demonstrated in PAH that this phenotype is, in part, because of the miR-223/DNA damage/Poly[ADP-ribose] polymerase 1/miR-204 axis activation and subsequent bromodomain protein 4 (BRD4) overexpression. Interestingly, BRD4 is also a trigger for calcification and remodeling processes, both of which are important in CAD. Thus, we hypothesize that BRD4 activation in PAH influences the development of CAD. Approach and Results—: PAH was associated with significant remodeling of the coronary arteries in both human and experimental models of the disease. As observed in PAH distal pulmonary arteries, coronary arteries of patients with PAH also exhibited increased DNA damage, inflammation, and BRD4 overexpression. In vitro, using human coronary artery smooth muscle cells from PAH, CAD and non-PAH–non-CAD patients, we showed that both PAH and CAD smooth muscle cells exhibited increased proliferation and suppressed apoptosis in a BRD4-dependent manner. In vivo, improvement of PAH by BRD4 inhibitor was associated with a reduction in coronary remodeling and interleukin-6 expression. Conclusions—: Overall, this study demonstrates that increased BRD4 expression in coronary arteries of patient with PAH contributes to vascular remodeling and comorbidity development. Abstract : Supplemental Digital Content is available in the text.